Ajustes e adaptações do exercício físico resistido de baixa intensidade e longas séries nas variáveis autonômicas, ventilatórias, musculares e hemodinâmicas em idosos com doença arterial coronariana - Caruso, Flávia Cristina Rossi (Universidade Federal de São Carlos, 2015)
The thesis consisted of three studies described below. The study I, entitled "Hemodynamic and metabolic response during aerobic and resistance dynamic exercise in different intensities: A cross-sectional study on implications of intensity on safety and symptoms in patients with coronary disease". Where the objective of this study was to evaluate the clinical and physiological responses during resistance exercise in loads of 30 and 60% of 1-RM on the leg press 45° and compare the responses with maximum aerobic exercise. The evaluation included aerobic test on cycle ergometer and resistance test in leg press 45°. Ventilation, hemodynamic and clinical measurements were performed. The results showed that 60% of resistance exercise and the dynamic test increased variables response studied in compared the load of 30% in resistance exercise. We conclude that high repetition of resistance exercise results in physiological changes at an intensity comparable to maximal aerobic exercise. Further, the study II, entitled "Resistance training improves heart rate variability and muscular performance: A randomized controlled trial in patients with coronary artery disease study" The objective was to investigate the effects of a high repetition program/low load resistance training (RT) (HR/LL-RT) in heart rate variability (HRV) in muscular strength and endurance in patients with CAD. Test were carried out in 1-RM test in leg press 45°, HRV was captured in the supine position before and after eight weeks of RT. The HR/LL-RT program consisted of an exercise using leg press 45°; (three sets, twenty repetitions, twice a week for eight weeks). The results showed that after eight weeks RT there was a significant increase in the values of the RMSSD, ApEn SD1 indices and only the TG (p<0.05). There was a significant decrease in Mean HR after RT for TG (p<0.05). Additionally, there was significant improvement in muscular strength and endurance only for the TG (p<0.05). We conclude that eight weeks of HR/LL-RT is a sufficient stimulus to change heart function, muscle strength and endurance in patients with CAD. Finally, the study III, entitled: ''What the impact of resistance training on hemodynamic, autonomic and metabolic variables in coronary artery disease patients? The randomized controlled trial of eight weeks''. Where the objective was to evaluate the hemodynamic, metabolic, and the HRV effects during maximum intensity tolerated in constant loads protocols during dynamic and resistance exercise before and after eight weeks of resistance training program of low intensity and high reps (RTLHr) in patients with CAD. The results showed increase in maximum and submaximal load (p<0.01) and attenuation of the hemodynamic performance in the higher load (p<0.01) and reduced lactate concentration compared for TG. During the cycle ergometer exercise, there was attenuation of hemodynamic performance and increased minute ventilation (p<0.01). Finally, the TRBAr produced greater parasympathetic contribution (RMSSD and SD1), after RT. We conclude that eight weeks of RTLHr may attenuate the hemodynamic stress, metabolic and autonomic during resistance exercise with cardiovascular and autonomic beneficial effects also in the dynamic exercise.
Keywords: Reabilitação cardíaca; Exercício resistido; Exercício aeróbio; Doença arterial coronariana; Cardiac rehabilitation; Resistance exercise; Aerobic exercise; Coronary artery disease; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL